Intensive support for adults with intellectual disability and behaviours that challenge: a survey of provision and service typologies in England. Issue 2 (March 2020) - Hassiotis, Angela; Walsh, Amy; Budgett, Jessica; Harrison, Isobel; Jones, Rebecca; Morant, Nicola; Courtenay, Ken; Crossey, Elisabeth Victoria; Hall, Ian; Romeo, Renee; Taggart, Laurence George; Langdon, Peter E.; et al.
Abstract : Background: Approximately 18% of adults with intellectual disabilities living in the community display behaviours that challenge. Intensive support teams (ISTs) have been recommended to provide high-quality responsive care aimed at avoiding unnecessary admissions and reducing lengthy in-patient stays. Aims: To identify and describe the geographical distribution and characteristics of ISTs, and to develop a typology of IST service models in England. Method: We undertook a national cross-sectional survey of 73 ISTs. A hierarchical cluster analysis was performed based on six prespecified grouping factors (mode of referrals, size of case-load, use of outcome measures, staff composition, hours of operation and setting of service). A simplified form of thematic analysis was used to explore free-text responses. Results: Cluster analysis identified two models of IST provision: (a) independent and (b) enhanced provision based around a community intellectual disability service. ISTs aspire to adopt person-centred care, mostly use the framework of positive behaviour support for behaviour that challenges, and report concerns about organisational and wider context issues. Conclusions: This is the first study to examine the delivery of intensive support to people with intellectual disability and behaviour that challenges. A two-cluster model of ISTs was found to have statistical validity and clinical utility. The clinical heterogeneity indicates that further evaluation of these service models is needed to establish their clinical and cost-effectiveness.